Towards implementing the WSIS agenda in Nigeria (2006)
This paper discusses the World Summit on the Information Society (WSIS). It made an overview of the first and the second phases of the WSIS and the documents generated from these meetings. The key issues around which the WSIS revolved were discussed and their implementations in and implications for Nigeria were elaborately highlighted. Some recommendations on how Nigeria can derive meaningful gains from the WSIS Agenda were provided.